A Case Report of Unusual Appearance of Multifocal Nodular Fatty Liver Infiltration with Hemosiderosis in A Patient with Leukemia, the Challenge in Diagnosis - M, El Khaldi; M, Al Hussaini; M, Abu Shattal; H, Abu Jazar; M, Swaidan (Archives of Clinical and Medical Case Reports, 2021)
Hepatic steatosis is a frequent finding in computed tomography (CT) and magnetic resonance imaging (MRI). Chemotherapy is a predisposing factor for both fatty liver infiltration and hemosiderosis. Unusual appearance and behavior of multiple focal nodular fatty infiltration is rare to encounter and when associated with history of malignancy and/or infection presents a dilemma that a confident diagnosis might not be rendered by MRI thus a diagnostic biopsy would be needed to resolve the uncertainty in diagnosis. We present a patient with second relapse of acute myelogenous leukemia (AML) who developed fungal pulmonary infection while receiving salvage chemotherapy. Progressive target-shaped focal liver lesions which demonstrated characteristic fatty signal intensity on MRI were seen along with features of hemosiderosis of the liver parenchyma. Target and non-target liver tru-cut biopsies had to be performed to reach the final diagnosis of focal fatty infiltration and to rule out the differential diagnosis of liver abscesses and leukemia infiltration.